I like books - Browne, Anthony (New York, N.Y. : Scholastic, Inc., 1988)
A young chimp declares his love for all kinds of books, from funny books and scary books to song books and strange books.
Keywords: Books and reading -- Fiction; Chimpanzees -- Fiction